Interação, Redes e comunidades de Prática (CoP): subsídios para a Gestão do Conhecimento na Educação - Mengalli, Neli Maria (2006)
This Master s Dissertation researches the disclosures derived from the curriculum of the School Administrators Development course in the use of Information and Communication Technologies of the School Administration and Technology Project, which emerged from the actions, practices, attitudes and discourse of the educational administrators from the public schools of Sao Paulo State and departments of education. These disclosures made explicit certain indications of knowledge based management through technological resources that empower the development of collaborative actions. Considering that the computer is a potential instrument for creating communities, the research shows the possible uses of technological resources for network building, problem solving, and decision making. Data collection instruments consisted of the forums and reflective memoirs written by the course participants in various roles; semi structured interviews with project members and instructors selected after review of the memoirs; and questionnaires regarding the topic of knowledge based management. After data analysis and interpretation, it was possible to perceive indications of knowledge based management in the schools, yet still enacted intuitively and unsystematically. Although the course project included the elements indicated by theorists as essential to knowledge based management, not all of these concepts were revealed in the data collection instruments. It was possible to perceive the potentials for the suggestion of network formation and community building, primarily Communities of Practice (CoP), as the basis for knowledge based management in Education.